2014
DOI: 10.5713/ajas.2013.13284
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mechanically Deboned Chicken Meat Hydrolysates on the Physicochemical Properties of Imitation Fish Paste

Abstract: This study investigated on the effects of adding mechanically deboned chicken meat (MDCM) hydrolysates on the quality properties of imitation fish paste (IFP) during storage. IFP was prepared from Alaska Pollack, spent laying hens surimi and protein hydrolysates which were enzymatically extracted from MDCM. The study was designed as a 3×4 factorial design with three MDCM hydrolysate content groups (0%, 0.4%, and 0.8%) and four storage times (0, 2, 4, and 6 weeks). Addition of MDCM hydrolysates increased crude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
4
0
3
Order By: Relevance
“…have reported that hydrolysates from fish and chicken have antioxidant potential and addition of the hydrolysates to minced beef prevented lipid oxidation with rates of 93% and 80%. The hydrolysates obtained from mechanically separated chickens showed a high rate of DPPH (2,2‐diphenyl‐1‐picrylhydrazyl) radical capture activity . Fishery by‐products are good sources for antioxidant peptides.…”
Section: Animal Based Preservativesmentioning
confidence: 99%
“…have reported that hydrolysates from fish and chicken have antioxidant potential and addition of the hydrolysates to minced beef prevented lipid oxidation with rates of 93% and 80%. The hydrolysates obtained from mechanically separated chickens showed a high rate of DPPH (2,2‐diphenyl‐1‐picrylhydrazyl) radical capture activity . Fishery by‐products are good sources for antioxidant peptides.…”
Section: Animal Based Preservativesmentioning
confidence: 99%
“…Ayrıca % 10'a kadar MATE ve % 2'ye kadar kollajen ilave edilmesinin ürünün duyusal özelliklerinde herhangi bir olumsuz etki oluşturmadığını rapor etmişlerdir. Son yıllarda, balık ve su ürünleri etinden elde edilen surimi, kamaboko, imitasyon paste, yengeç stick gibi et ürünlerinin üretiminde MAKE ilavesinin, bu yan ürün için yeni bir kullanım alanı oluşturduğu belirlenmiştir (11,26,27).…”
Section: Kullanım Alanlarıunclassified
“…Yapılan çalışmalarda, MATE'den elde edilen protein hidrolizatları bazı ürünlerde katkı olarak kullanılmış, bunun ürünlerde iyi bir jel ve tekstür oluşturduğu, TBAR maddelerin azaldığı, anjiyotensin dönüştüren enzim aktivitesinin inhibe edildiği ve serbest radikal süpürücü aktivitenin ise arttığı belirlenmiştir. Sonuçta, MATE'lerden elde edilen protein hidrolizatlarının eklendiği ürünlerde elde edilen teknolojik avantajların yanı sıra sağlık açısından da olumlu etkiler meydana getirdiği tespit edilmiştir (26,27 bendinde ise mekanik ayrılmış kırmızı etlerin et ürünü üretiminde kullanılamayacağı, sadece ihracat amaçlı üretilen bu etlerin ve ürünlerinin onaylı işletmeler arası sevkine ihracat yapılması kaydı ile izin verildiği belirtilmiştir. Aynı tebliğin et ürünleri özel ürün özellikleri kısmında madde 9'un 4 bendinde ise MAKE'nin sadece ısıl işlem görmüş kanatlı emülsifiye et ürünlerinin üretiminde kullanılmak üzere entegre işletmeler tarafından üretilmesine ve üretilen MAKE'nin aynı amaç doğrultusunda diğer onaylı işletmelere sevkine yeniden izin verilmiştir.…”
Section: Kullanım Alanlarıunclassified
See 1 more Smart Citation
“…The lipid content makes MDM hydrolysate extremely susceptible to oxidation and degradation during processing, excessive lipids may adversely affect quality, due to oxidised lipids interacting with proteins, which could result in off-flavour of the protein product (Jin et al, 2014). For production of meat hydrolysates, according to our results, the enzyme was selected, the degree of hydrolysis and the changes in the protein composition of hydrolysates were examined, and allergenic activity and the sensory properties were considered.…”
Section: Resultsmentioning
confidence: 99%